Relationship Between Pregnant Women's Knowledge of Iron (Fe) Tablets and Incidence of Anemia at PMB Shinta, Medan Polonia District, North Sumatera Province - Friza Situmorang; Henny Rista; Dessy Ratna Sari; Yasrida Nadeak; Eva Dona Sinaga; Nita Nasefa (Asosiasi Dosen Muda Indonesia, 2026)
Anemia during pregnancy remains a major public health problem in Indonesia. One of the contributing factors is inadequate maternal knowledge regarding iron (Fe) tablets, which may affect adherence to supplementation and increase the risk of anemia. Objective: This study aimed to analyze the relationship between pregnant women's knowledge of iron (Fe) tablets and the incidence of anemia at PMB Shinta, Medan Polonia District, North Sumatera Province, in 2025. Methods: This quantitative study employed a cross-sectional design. The study involved all 30 pregnant women attending antenatal care at PMB Shinta, selected through total sampling. Data were collected using a structured questionnaire and hemoglobin examination. The data were analyzed using descriptive statistics and the Chi-Square test. Findings: The results showed that 56.7% of respondents had poor knowledge and 60.0% experienced anemia. A significant relationship was found between maternal knowledge and the incidence of anemia, with a p-value of 0.013. Pregnant women with poor knowledge had a 10.5-times higher likelihood of experiencing anemia than those with good knowledge (OR = 10.5; 95% CI: 1.889–58.359). Implications: The findings indicate the need to strengthen health education during antenatal care, particularly regarding the benefits, dosage, timing, and proper consumption of iron tablets. Improved maternal knowledge is expected to support adherence to iron supplementation and reduce the incidence of anemia during pregnancy. Originality: This study provides recent empirical evidence from a primary midwifery practice in Medan Polonia by directly examining the relationship between maternal knowledge of iron tablets and anemia incidence. The findings offer practical value for developing targeted, community-based maternal health education strategies.